Pengembangan Karakter Anak di Indonesia Heritage Foundation (IHF) Depok - Faujiah, Ajri; Tafsir, Ahmad; Sumadi, Sumadi (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2018)
Character is something that is reflected in human beings through their words, actions and movements in daily life. Good characters are expected by everyone. Indonesia has sparked 18 national character values that must be owned by its citizens. Characters will be formed through daily habituation that is done consistently, exemplary and repetitive. One environment that helps the development of children's character is the school environment, where habituation in the school environment must be in line with habituation in the home environment and community environment. This article was written to look at how the school environment can help in character development, by taking one of the schools that focuses on students' character education, namely the character school in the Indonesia Heritage Foundation (IHF) Depok, in terms of its education management and education model.